Evaluation of gaps in direct oral anticoagulants (DOACs) management in an outpatient underserved clinic: a cross-sectional study - Bader M. Alghamdi; Sara L. Rogers (Scientific Reports)
Abstract DOACs are widely used for stroke prevention in non-valvular atrial fibrillation and treatment of thromboembolism, but gaps in their management can lead to adverse outcomes. In outpatient, underserved clinics, challenges such as inappropriate dosing, lack of monitoring, and improper drug combinations may be more pronounced, necessitating evaluation to optimize patient care and reduce risks. This study assessed the appropriateness of DOAC use and dosing per FDA guidelines, considering renal function, hepatic function, and drug–drug interactions. Secondary objectives focused on evaluating inappropriate aspirin use alongside DOACs. This was a single-center retrospective cohort study. The study was conducted at Texas A&M Health Family Care Clinic (12/24/2022–12/24/2023). Older than 18 years of age and had active prescription of DOAC (apixaban, dabigatran, edoxaban, or rivaroxaban). A total of 125 DOAC patients were included. Inappropriate dosing based on renal function occurred in 16% of cases. DOAC use was unsuitable in two patients with severe hepatic impairment. Major drug interactions resulted in two instances of inappropriate DOAC use. Additionally, about 61% of aspirin usage involved inappropriate combinations with DOACs, as shown in Fig. 1. The study’s findings indicate that anticoagulation management in our ambulatory care setting has the potential for further optimization.